The Sullivanians : sex, psychotherapy, and the wild life of an American commune - Stille, Alexander (Farrar, Straus and Giroux, 2023)
"The shocking story of the Sullivan Institute, a psychoanalytic organization of artists and intellectuals that devolved into a dangerous cult on Manhattan's Upper West Side"--